Students' Perception of the Blended Learning Method for Teaching Oral Pathology - Mehwish Feroz Ali; Gulrukh Askary; Farwa Sajjad (ziauddin University, 2024)
Background: In the present Covid environment, blended learning methodologies helped students stay interested in their academic work and the learning process. Our educational systems have undergone a revolution attributable to technology and e-learning resources.  In this study, the DREEM questionnaire was used to assess students' perceptions of learning satisfaction and environment. We compared the learning outcomes (end-of-course test results) of an oral pathology course taught to third-year dental students by using a blended learning method. Methods: A longitudinal observational study from March to November 2021 was conducted by researchers at Fatima Jinnah Dental College and Hospital in Karachi, Pakistan, in the Department of Oral Pathology. In the blended learning approach, interactive online lectures, recorded videos with post quizzes, cased-base discussions, concept maps and individual presentations were integrated into the curriculum. The paired sample t-test was used to make the above comparisons, and a p-value <0.05 was considered significant. Results: There were 50 (62.5 percent) females and 30 (37.5 percent) males. In terms of student satisfaction with the educational environment and content knowledge, the DREEM scores in the blended learning group (35.59±4.84) were significantly (p<0.001) higher compared to the conventional learning group (30.86±3.53). Moreover, the blended learning mean post-test score (20.25±2.16 [95% CI 19.7-20.7]) was also significantly higher than the Conventional learning method (14.02±3.65 [95% CI 13.2-14.8]). Conclusion: The current study found that blended learning had a positive effect on students' perceptions of the educational environment and subject knowledge. They performed better on the blended learning approach, oral pathology end-of-course MCQ-based test. Keywords: Dentistry; Medical Education; Oral Pathology; Distance Learning; Active Learning.